Surdez em linhas de fuga: políticas de subjetividades outras na educação inclusiva - Monti, Luísa Leôncio (2023)
The various obstacles imposed on the implementation of the inclusive education have made its effective implementation impossible. As a thesis, I assume that the subjecting violence manifests itself in the inclusive context, through normative logic, activated in the classification and categorization of disabled bodies and their affections. This movement weakens plural forms of life and, therewith, to maintain singularities, some bodies rise up, establishing resistance through lines of flight. In this sense, I aimed to map the practices of (non) violence in inclusive education composed of molar, molecular and lines of flight that act in the production of subjective marks in the deaf ethos. This is a cartographic research, based on a paradigmatic case, carried out in a school unit located in the interior of the state of São Paulo, in the high school stage. In school cartography, I problematized the practices of deaf subjectivation arising from the relations of knowledge and power produced in school discursive practices. I turned to the internal and capillary productions of/in the school, through the eyes of the deaf person, as well as about their insertion in inclusive educational practices. The field research took place on two fronts: observations in the school territory, with entries in a field diary and an interview, as a cartographic procedure. We opted for a cartographic analysis, conceptually based on the philosophies of difference. The theoretical reference came from Michel Foucault, Gilles Deleuze, and Félix Guattari. Were identified, interspersed with the narrative of the life poem, four molar lines (linguistic, physical space, affective and symbolic-religious violence) and four molecular lines (non-violence of the encounter, of being queer, of being umbandista, and other deafness), which guided the discussions. It is believed that the research contributes to recognizing aspects that lead to violence and non-violence in the constitution of subjectivity during the school trajectory of deaf people. In view of the signs found, there is a way of existence, a pragmatic of singularity in the life-poem, and that their voices/experiences in common rooms and the inclusive school stand as local knowledge that resists and announces more ethical practices in favor of differences made along lines of flight.